Correction: Effect of LiH on the fast hydrolysis and hydrogen generation of MgH2 by ball milling. (17th November 2022) - Qiu, Hongwei; Han, Xingbo; Zang, Shuyan; Liu, Wei; Yang, Guo; Lv, Lijun; Wang, Xiaofeng; Duan, Jiaqi; Wang, Shuangyu
Abstract : Correction for 'Effect of LiH on the fast hydrolysis and hydrogen generation of MgH2 by ball milling' by Hongwei Qiu et al., New J. Chem., 2022, 46, 19900–19908, ; https://doi.org/10.1039/D2NJ03496D .